Predictive capacity of boar sperm morphometry and morphometric sub-populations on reproductive success after artificial insemination - Barquero, Vinicio; Roldan, Eduardo R. S.; Soler, Carles; Yániz, Jesús L.; Camacho, Marlen; Valverde-Abarca, Anthony (Animals, 2021)
The efficiency of swine production measured as litter size influences the prof itability of the pig industry. Furthermore, sow fertility potential depends in part on the boar semen quality and reproductive efficiency. The objective of this study is to compare boar sperm head size and morphometric features of shape to evaluate their relationships with reproductive success after artificial insemination (AI). A morphometric analysis of boar ejaculate reveals morphometrically separate sub-populations. The differences between sub-populations are displayed for sperm head size. In addition, sperm clustering into sub-populations did not have a predictive capacity on lit ter size variables. Nevertheless, the morphometric variables of the sperm may have a predictive, albeit reduced, capacity regarding litter size variables. The results of this study therefore open up possibilities for future assessments of fertility.
Animals, volumen 11 (Mar, 2021):2-15
Keywords: Cerdos; Espermatozoides; Reproducción animal; Casa MorphPrograma para computador